Geometric morphometric discrimination of the three African honeybee subspecies Apis mellifera intermissa, A. m. sahariensis and A. m. capensis (Hymenoptera, Apidae): Fore wing and hind wing landmark configurations - Barour,C; Baylac, M. (My University, 2016)
In this study, a landmark-based geometric morphometric analysis was carried out on three honeybee subspecies: Apis m. intermissa and A. m. sahariensis collected from Algeria, and, as a reference, A. m. capensis collected from South Africa. The aim of this study was to discriminate honeybee subspecies by patterns of shape variation of fore and hind wings. A total of 540 wings from 270 honeybee workers were analyzed. Our results revealed very high cross-validation classification rates (96.7% based on fore wing shape and 99.6% based on the combination of fore and hind wing forms respectively). Discrimination was better using shape and form (shape + centroid size) of the fore wings than of the hind wings. The wing form parameters were found to differ significantly in shape and centroid size among the three analyzed subspecies. Finally, it may be concluded that landmark-based geometric morphometrics could be a powerful tool to characterize the Algerian honey bees